Analisis ekonomi kreatif dan industri halal untuk peningkatan ekonomi berbasis desa wisata Pandansari Warungasem Kab. Batang - aqil, rafid naufal; Adinugraha, Hendri Hermawan (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the role of the creative economy and the halal industry in supporting the development of village-based tourism, with a case study in Pandansari Tourism Village, Warungasem, Batang Regency. Using a qualitative descriptive approach through literature review, the research identifies potentials, challenges, and relevant development strategies. The findings reveal that the synergy between creative economy subsectors such as culinary, handicrafts, cultural arts, and digital-based attractions and the application of halal industry principles creates sustainable added value while strengthening local cultural identity. This integration not only enhances the attractiveness of the destination for Muslim tourists but also contributes to the establishment of an inclusive, competitive, and sustainable tourism ecosystem. Furthermore, the active involvement of local communities through the community-based tourism model plays a key role in fostering a sense of ownership and ensuring the village’s socio-economic sustainability. Supported by digital technology and creative marketing strategies, Pandansari Tourism Village has the potential to expand its promotional reach to global markets. This study highlights the importance of collaboration between local communities, government, and business actors in realizing a globally competitive halal-creative tourism village.